Contribution of livestock in livelihood: Ladakh region - AKAND, AFZAL HOQUE; SINGH, B P; CHANDER, MAHESH (The Indian Journal of Animal Sciences, 2017)
Contribution of livestock in terms of income, milk based nutrition, man days generated, FYM, socio-cultural importance was assessed among 120 livestock farmers of Ladakh in Jammu and Kashmir. Data were collected using semi-structured interview schedule. The study revealed that livestock’s contribution towards total house hold income ranged from 16.32 to 86.59%. Milk contributed about 1/3rd of dietary fat requirement of the farmers except among the farmers of Nyoma block where it contributed more than 80%. Similar trend was also observed in milk based protein (22-25%) and calcium intake (5-6%) in fulfilling the family requirement of Kargil, TSG and Chochut blocks. FYM obtained by the farmers was highest in Chochut (1.99 q/year) and lowest in Nyoma (0.67 q/year). But employment (man days/year) generated by livestock enterprise was more in Nyoma (561.91) as compared to the famers of other blocks that ranged from 294.11 to 326.67 per annum per family. Use of animal for mitigating the uncertainties in the region was not a common practice.